1993
DOI: 10.1136/ard.52.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Significance of enzyme linked immunosorbent assay (ELISA) for antibodies to double stranded and single stranded DNA in patients with lupus nephritis: correlation with severity of renal histology.

Abstract: The correlation between renal histology and class specific (IgG and IgM) antibodies to double stranded DNA (dsDNA) and single stranded DNA (ssDNA) was studied by enzyme linked immunosorbent assay (ELISA) in 40 untreated patients with systemic lupus erythematosus (SLE). The levels of IgG antibodies to dsDNA were significantly higher in patients with World Health Organisation class IV nephritis than in those with class I, class II, or class III nephritis. IgG antibodies to ssDNA were higher in patients with clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
78
0
3

Year Published

1994
1994
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(85 citation statements)
references
References 22 publications
4
78
0
3
Order By: Relevance
“…However, it should be mentioned that the correlation was not perfect, since 5 of the 10 patients with the highest antichromatin reactivity did not display proteinuria. Protein in the urine is not a sensitive indication of all forms of renal disease because glomerular damage as judged by microscopic examination of biopsies was not well correlated to proteinuria (47). Renal biopsies were not performed in the present study.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…However, it should be mentioned that the correlation was not perfect, since 5 of the 10 patients with the highest antichromatin reactivity did not display proteinuria. Protein in the urine is not a sensitive indication of all forms of renal disease because glomerular damage as judged by microscopic examination of biopsies was not well correlated to proteinuria (47). Renal biopsies were not performed in the present study.…”
Section: Resultsmentioning
confidence: 76%
“…In some studies, the presence of anti-nDNA has been correlated with the severity of disease and the presence of lupus nephritis (25,46,47), especially if changes in antibody levels over time are considered (48,49). In other studies no significant correlation between disease and anti-nDNA was found (50,51 ).…”
Section: Resultsmentioning
confidence: 99%
“…Autoantibodies are thought to have a primary role in the pathogenesis of SLE. Levels of circulating autoantibodies correlate with disease severity in both SLE patients and MRL-Fas lpr mice, with IgG1 and IgG2 being the predominant subclasses found (33,34). These autoantibodies are thought to play a causative role in the occurrence of disease given that a rise in circulating autoantibodies is seen in SLE patients before renal relapses and before any disease is evident in lupus-prone mice (31,35).…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenetic significance of anti-DNA antibodies has been implicated by their correlation with disease activity (29 -31) and their deposition at sites manifesting histopathologic changes (32)(33)(34)(35). It would be of interest to spec- Our findings demonstrate the binding of anti-DNA antibodies to the HMC cell surface and intracellularly, while no staining was observed within the extracellular matrix.…”
Section: Discussionmentioning
confidence: 99%